Preparation and application of carbon nitride / indium zinc sulfide / polyacid composite material
By constructing a tubular carbon nitride/indium zinc sulfide/polyacid composite, the problems of poor stability of polyacid substances in solution and low catalytic performance in hydrogen production are solved, and the efficient photocatalytic water decomposition and hydrogen production effect is achieved.
Patent Information
- Application Number
- CN202411819764.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
As photocatalytic materials, polyacid substances have poor stability in solution and have low hydrogen production catalytic performance.
By combining carbon nitride, indium zinc sulfide and polyacid, a tubular carbon nitride/indium zinc sulfide/polyacid composite material is constructed, and the special tubular structure of carbon nitride and the high conductivity of the polyacid are used to improve the stability of the photocatalyst and hydrogen production efficiency.
A polyacid-based composite material with high photocatalytic activity and stability has been achieved, and the efficiency of photocatalytic water decomposition and hydrogen production is improved.
Smart Images

Figure CN119633901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a carbon nitride / indium zinc sulfide / polyacid composite material. Background Art
[0002] With the rapid development of industry, problems such as resource shortage, energy crisis and environmental pollution have become increasingly prominent. Hydrogen energy is a clean, non-toxic and high calorific value clean energy. The product of its combustion is water, and it does not produce greenhouse gas CO. 2 and NO, NO 2 、SO 2 and other air pollutants.
[0003] At present, fossil energy steam thermal reforming is the mainstream method of hydrogen production, but the process relies on fossil fuels and is costly. In contrast, photocatalytic water decomposition to produce hydrogen can utilize solar energy and water resources, and is one of the most promising methods for achieving green technology innovation and energy structure adjustment in the context of carbon neutrality. However, the industrialization of photocatalytic hydrogen production technology still needs to overcome difficulties such as low photocatalyst efficiency, complex preparation, small specific surface area, secondary pollution and narrow range of light energy utilization. Therefore, the development of efficient, stable and recyclable photocatalysts is crucial to promoting the development of the photocatalytic hydrogen production industry.
[0004] Polymetallic oxygen clusters, referred to as polyacids, are inorganic metal oxygen clusters with diverse structures. They are highly stable and have strong electron transport capabilities. However, polyacids are easily aggregated and have strong water solubility, which limits their direct application in the field of photocatalysis. Indium zinc sulfide is a semiconductor photocatalyst with a large specific surface area layered structure. Its preparation method is simple and its morphology is controllable, but it has disadvantages such as fast recombination rate of photogenerated charge carriers, which limits its development. As a new type of non-metallic polymer semiconductor photocatalytic material, carbon nitride has excellent physical and chemical stability, acid and alkali resistance, and is easy to form a π delocalized conjugated system similar to benzene rings, so it has a unique electronic structure and good optical properties. Therefore, we used tubular carbon nitride as a carrier and constructed a tubular carbon nitride / indium zinc sulfide / polyacid composite material through an in situ growth method, and obtained a polyacid-based composite material with high photocatalytic activity and stability for photocatalytic water decomposition to produce hydrogen. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that polyacids as photocatalytic materials have poor stability in solution and low hydrogen production catalytic performance. In order to improve its hydrogen production performance, the present invention provides a preparation method and application of a carbon nitride / indium zinc sulfide / polyacid composite material.
[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:
[0007] 1. Preparation of carbon nitride precursor: Add melamine, urea and thiocyanate to anhydrous ethanol, stir for 3 hours, and place at room temperature to allow the solvent to evaporate naturally to obtain a precursor of carbon nitride preparation material.
[0008] 2. Preparation of carbon nitride: A certain amount of the precursor is weighed and calcined in a tubular furnace. After the reaction is completed, a sample is taken out to obtain carbon nitride.
[0009] 3. Preparation of carbon nitride / indium zinc sulfide heterogeneous material: The carbon nitride is added to a flask containing distilled water. After ultrasonication, indium chloride, zinc chloride, and thioacetamide are added and stirred for 30 minutes. Then, it is placed in an oil bath and refluxed for 7 hours. The product is washed several times with deionized water and anhydrous ethanol, and the product is collected after centrifugation and dried to obtain the carbon nitride / indium zinc sulfide heterogeneous material.
[0010] 4. Preparation of carbon nitride / indium zinc sulfide / polyacid composite material: The carbon nitride / indium zinc sulfide heterogeneous material is added to HCl-Tris buffer solution, and cobalt-substituted phosphotungstate Na 10 [Co 4 (H 2 O) 2 (α-PW 9 O 34 )], then dopamine hydrochloride was added and stirred for 8 hours, centrifuged, washed with ethanol and water three times and then vacuum dried to obtain a carbon nitride / indium zinc sulfide / polyacid composite material.
[0011] In the preparation of the composite material, the molar ratio of melamine, urea and thiocyanuric acid in step 1 is 1:1:(1.8-2.3);
[0012] In the preparation of the composite material, the temperature gradient of the tube furnace in step 2 is 5°C / min, and the material is heated at 550°C for 3 hours;
[0013] In the preparation of the above composite material, the molar ratio of indium chloride, zinc chloride and thioacetamide in step 3 is 1:1:(1.5-2.5);
[0014] In the preparation of the composite material, the rotation speed of the centrifugal operation in step 3 is 4000r / min to 5000r / min;
[0015] In the preparation of the composite material, the drying temperature in step 3 is 60°C to 80°C, and the drying time is 10 hours to 12 hours;
[0016] In the preparation of the composite material, the carbon nitride / indium zinc sulfide heterogeneous material and the cobalt-substituted phosphotungstate Na 10 [Co 4 (H2 O) 2 (α-PW 9 O 34 )] The feed mass ratio is 1:(0.7~0.8);
[0017] In the preparation of the composite material, the rotation speed of the centrifugal operation in step 4 is 4000r / min to 5000r / min;
[0018] In the preparation of the composite material, the drying temperature in step 4 is 60°C to 80°C, and the drying time is 10 hours to 12 hours;
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention uses organic substances such as melamine, urea, and thiocyanuric acid to prepare tubular carbon nitride, and successfully grows indium zinc sulfide on the surface of the tubular carbon nitride in situ by a thermal reflux synthesis method with indium chloride, zinc chloride, and thioacetamide to obtain a tubular carbon nitride / indium zinc sulfide / polyacid composite material. The results of electron scanning microscopy show that the material prepared by the present invention is a composite material with a sheet structure grown on the surface of a special tubular structure.
[0021] The special tubular structure of the composite material is due to the morphology of the carbon nitride substrate. The special tubular structure of carbon nitride increases the specific surface area, allowing indium zinc sulfide to grow on the surface of carbon nitride during the synthesis process. At the same time, highly conductive dopamine hydrochloride is introduced as a binder, and polyacids are loaded on the flaky indium zinc sulfide by physical stirring. Adding an appropriate amount of polyacids and binders does not change the flaky structure of indium zinc sulfide.
[0022] The invention uses dopamine hydrochloride as a binder to attach a cobalt-substituted polyacid to the surface of a carbon nitride / indium zinc sulfide having a tubular sheet multi-level structure, thereby obtaining a carbon nitride / indium zinc sulfide / polyacid composite material for the first time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of a carbon nitride monomer prepared in Example 1 of the present invention.
[0024] Figure 2 This is a scanning electron microscope image of a carbon nitride monomer prepared in Comparative Example 1 of the present invention.
[0025] Figure 3 This is a scanning electron microscope image of a carbon nitride monomer prepared in Comparative Example 2 of the present invention.
[0026] Figure 4 This is a scanning electron microscope image of the carbon nitride / indium zinc sulfide heterogeneous material prepared in Example 2 of the present invention.
[0027] Figure 5 This is a scanning electron microscope image of the tubular carbon nitride / indium zinc sulfide / polyacid composite material provided in Example 3 of the present invention.
[0028] Figure 6 FT-IR graphs of carbon nitride, carbon nitride / indium zinc sulfide heterogeneous material, and carbon nitride / indium zinc sulfide / polyacid composite material provided in Embodiment 1, Embodiment 2, and Embodiment 3 of the present invention.
[0029] Figure 7 XRD comparison diagrams of carbon nitride, carbon nitride / indium zinc sulfide heterogeneous material, and carbon nitride / indium zinc sulfide / polyacid composite material provided in Embodiment 1, Embodiment 2, and Embodiment 3 of the present invention.
[0030] Figure 8 This is a photocatalytic hydrogen production performance diagram of a tubular carbon nitride / indium zinc sulfide / polyacid composite material described in the present invention at room temperature and pressure. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0032] Implementation Case 1
[0033] This embodiment provides a carbon nitride photocatalyst, which is prepared according to the following method:
[0034] Melamine, urea, and thiocyanate were dissolved in 30 mL of anhydrous ethanol at a molar mass ratio of 1:1:2. After stirring for 3 hours, the mixture was placed at room temperature to allow the solvent to evaporate naturally, thereby obtaining a precursor for the carbon nitride preparation material.
[0035] The precursor is placed in a tube furnace and heated at 550° C. for 3 hours at a temperature increase gradient of 5° C. / min. After the reaction is completed, a sample is taken out to obtain carbon nitride.
[0036] Implementation Case 2
[0037] This embodiment provides a carbon nitride / indium zinc sulfide heterogeneous photocatalyst, which is prepared according to the following method:
[0038] Melamine, urea, and thiocyanate were dissolved in 30 mL of anhydrous ethanol at a molar mass ratio of 1:1:2. After stirring for 3 hours, the mixture was placed at room temperature to allow the solvent to evaporate naturally, thereby obtaining a precursor for the carbon nitride preparation material.
[0039] The precursor is placed in a tubular furnace and calcined at a temperature gradient of 5°C / min and heated at 550°C for 3 hours. After the reaction is completed, a sample is taken out to obtain tubular carbon nitride;
[0040] Take 100 mg of the above carbon nitride and add it to distilled water. After ultrasonication, indium chloride, zinc chloride and thioacetamide are added respectively and stirred for 30 minutes. Then, it is placed in an oil bath pot and refluxed at 80°C for 7 hours, and washed with deionized water and anhydrous ethanol. After centrifugation, it is collected and dried to obtain a carbon nitride / indium zinc sulfide heterogeneous material.
[0041] Implementation Case 3
[0042] This embodiment provides a carbon nitride / indium zinc sulfide / polyacid composite photocatalyst, which is prepared according to the following method:
[0043] Melamine, urea, and thiocyanate were dissolved in 30 mL of anhydrous ethanol at a molar mass ratio of 1:1:2. After stirring for 3 hours, the mixture was placed at room temperature to allow the solvent to evaporate naturally, thereby obtaining a precursor for the carbon nitride preparation material.
[0044] The precursor is placed in a tube furnace and calcined at a temperature gradient of 5°C / min and heated at 550°C for 3 hours. After the reaction is completed, a sample is taken out to obtain carbon nitride;
[0045] Take 100 mg of the above carbon nitride and add it to distilled water. After ultrasonication, indium chloride, zinc chloride, and thioacetamide are added and stirred for 30 minutes. Then, the reaction system is placed in an oil bath pot and heated under reflux in the oil bath and stirred for 7 hours. The reaction system is washed with deionized water and anhydrous ethanol, collected after centrifugation, and dried to obtain a carbon nitride / indium zinc sulfide heterogeneous material. The carbon nitride / indium zinc sulfide heterogeneous material is added to an HCl-Tris buffer solution, and cobalt-substituted phosphotungstate (NH 4 ) 5 PW 11 CoO 39 , then add 10 mg of dopamine hydrochloride and stir for 8 hours, centrifuge, wash three times with ethanol and water, and then vacuum dry to obtain a tubular carbon nitride / indium zinc sulfide / polyacid composite material.
[0046] Comparative Case 1
[0047] The carbon nitride photocatalyst provided in this comparative case is different from that in Example 1 in that 4 g of melamine, urea and thiocyanate are added in a molar mass ratio of 1:1:1.
[0048] Comparative Case 2
[0049] The carbon nitride photocatalyst provided in this comparative example is different from that in Example 1 in that 4 g of melamine, urea and thiocyanate are added in a molar mass ratio of 1:1:3.
[0050] The present invention will be further described below in conjunction with the accompanying drawings:
[0051] Figure 1 This is an electron scanning image of the carbon nitride substrate of a carbon nitride / indium zinc sulfide / polyacid composite material in Example 1 of the present invention. It can be seen that the carbon nitride substrate is a tubular structure.
[0052] Figure 2 This is an electronic scan of carbon nitride in which melamine, urea and thiocyanuric acid are fed in a molar mass ratio of 1:1:1 in comparative example 1 of the present invention.
[0053] Figure 3 This is an electronic scanning diagram of carbon nitride in which melamine, urea and thiocyanuric acid are fed in a molar mass ratio of 1:1:3 in comparative example 2 of the present invention.
[0054] Figure 4 This is a scanning electron microscope image of the tubular carbon nitride / indium zinc sulfide heterogeneous material prepared in Example 2 of the present invention. It can be seen that after the in-situ growth of indium zinc sulfide on carbon nitride, in-situ growth of indium zinc sulfide follows the original structure, and the tubular structure of carbon nitride is still very obvious, which provides more sites for the loading of indium zinc sulfide on carbon nitride.
[0055] Figure 5 This is a scanning electron microscope image of the carbon nitride / indium zinc sulfide / polyacid composite material provided in Example 3 of the present invention. After adding appropriate amounts of dopamine hydrochloride and polyacid, it is observed that the morphology of the carbon nitride-indium zinc sulfide composite material has no obvious change.
[0056] Figure 6 The FT-IR images of carbon nitride, carbon nitride / indium zinc sulfide, and carbon nitride / indium zinc sulfide / polyacid composite materials provided in Example 1, Example 2, and Example 3 of the present invention, wherein the characteristic peaks thereof indicate the successful preparation of the composite materials.
[0057] Figure 7 The XRD comparison diagram of the carbon nitride / indium zinc sulfide / polyacid composite monomer provided in Example 1, Example 2, and Example 3 of the present invention. In the composite material, since dopamine hydrochloride uniformly loads the polyacid and the loading amount is small, Na 10 [Co 4 (H 2 O) 2 (α-PW 9 O 34 )]’s XRD characteristic peaks.
[0058] Figure 8 This is a photocatalytic hydrogen production performance diagram of a carbon nitride / indium zinc sulfide / polyacid composite material described in the present invention at room temperature and pressure. The photocatalytic hydrogen production performance of the material provided can reach up to 11.5mmol·g in five hours. -1 ·h -1 .
[0059] In summary: the carbon nitride / indium zinc sulfide / polyacid composite material of Example 3 of the present invention is prepared in multiple steps and can be used for photocatalytic decomposition of water to produce hydrogen. The addition of polyacid enhances the photocatalytic decomposition of water to produce hydrogen efficiency of the material. Carbon nitride as a substrate solves the problem of easy agglomeration of indium zinc sulfide, and improves the separation of photogenerated electrons and photogenerated holes for indium zinc sulfide. A carbon nitride / indium zinc sulfide / polyacid composite material has great potential in photocatalytic decomposition of water.
Claims
1. A method for preparing a carbon nitride / indium zinc sulfide / polyacid composite material, characterized in that: The method comprises the following steps: using carbon nitride synthesized by mixing melamine, thiocyanate and urea in a certain proportion as a precursor; growing sheet-like indium zinc sulfide on the carbon nitride by heat reflux to obtain a carbon nitride / indium zinc sulfide heterogeneous material; finally, adding the heterogeneous material to a HCl-Tris buffer solution with a pH of 8.5, ultrasonically dispersing the solution, adding dopamine hydrochloride as a binder, and cobalt-substituted phosphotungstate Na 10 [Co4(H2O)2(α-PW9O 34 )] to obtain a tubular carbon nitride / indium zinc sulfide / polyacid composite material; The polyacid-based material is a tubular carbon nitride-indium zinc sulfide shell structure. The preparation method of the tubular carbon nitride / indium zinc sulfide / polyacid composite material comprises: (1) adding melamine, urea and thiocyanate to anhydrous ethanol, stirring for 3 hours, and then placing at room temperature to allow the solvent to evaporate naturally, thereby obtaining a precursor for preparing carbon nitride materials; (2) weighing a certain amount of the precursor and calcining it in a tube furnace, taking out a sample after the reaction is completed, and obtaining carbon nitride; (3) adding the carbon nitride to distilled water, adding indium chloride, zinc chloride, and thioacetamide after ultrasonication, and stirring for 30 minutes, then placing the reaction system in an oil bath, heating under reflux, and stirring for 7 hours, and washing with deionized water and anhydrous ethanol, collecting after centrifugation, and drying to obtain a carbon nitride / indium zinc sulfide heterogeneous material; (4) Add the carbon nitride / indium zinc sulfide heterogeneous material to HCl-Tris buffer solution, add cobalt-substituted phosphotungstate Na 10 [Co4(H2O)2(α-PW9O 34 )], then dopamine hydrochloride was added and stirred for 8 hours, centrifuged, washed three times with ethanol and water and then vacuum dried to obtain a tubular carbon nitride / indium zinc sulfide / polyacid composite material.
2. The method for preparing the carbon nitride / indium zinc sulfide / polyacid composite material according to claim 1, characterized in that: In the step (1), the molar ratio of melamine, urea and thiocyanuric acid is 1:1:(1.8-2.3).
3. The method for preparing the carbon nitride / indium zinc sulfide / polyacid composite material according to claim 1, characterized in that: In the step (2), the temperature rise gradient of the tubular furnace is 5°C / min, and heating is performed at 550°C for 3h.
4. The method for preparing the tubular carbon nitride / indium zinc sulfide / polyacid composite material according to claim 1, characterized in that: In the step (3), the molar ratio of indium chloride, zinc chloride and thioacetamide is 1:1:(1.5-2.5); The speed of centrifugal operation is 4000r / min~5000r / min; Drying temperature: 60℃~80℃, drying time: 10h~12h; 5. The method for preparing the carbon nitride / indium zinc sulfide / polyacid composite material according to claim 1, characterized in that: In the step (4), the carbon nitride / indium zinc sulfide heterogeneous material and the cobalt-substituted phosphotungstate Na 10 [Co4(H2O)2(α-PW9O 34 )] The feed mass ratio is 1:(0.7~0.8); The speed of centrifugal operation is 4000r / min~5000r / min; The drying temperature is 60℃~80℃, and the drying time is 10 hours~12 hours; The material prepared by this method has excellent visible light absorption ability and unique tubular structure, improves the photosensitivity of carbon nitride / indium zinc sulfide / polyacid composite materials, and realizes application in photocatalytic hydrogen production.
Citation Information
Cited By
Photocatalytic nano composite material as well as preparation method and application thereof
CN120502351A